2022
DOI: 10.1186/s12974-022-02558-z
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant attenuates NLRC4-dependent neuronal pyroptosis via NK1R/PKCδ pathway in a mouse model of intracerebral hemorrhage

Abstract: Background Pyroptosis is a programmed cell death mediated by inflammasomes. Previous studies have reported that inhibition of neurokinin receptor 1 (NK1R) exerted neuroprotection in several neurological diseases. Herein, we have investigated the role of NK1R receptor inhibition using Aprepitant to attenuate NLRC4-dependent neuronal pyroptosis after intracerebral hemorrhage (ICH), as well as the underlying mechanism. Methods A total of 182 CD-1 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(81 reference statements)
1
8
0
Order By: Relevance
“… 13 In contrast, knocking down NLRC4 using siRNA exerted neuroprotective effects in experimental intracerebral hemorrhage. 20 In addition, similar results were found in ischemic stroke using siRNA knockdown of NLRC4. 14 In the current study, serum NLRC4 levels were independently correlated with serum C-reactive protein levels.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“… 13 In contrast, knocking down NLRC4 using siRNA exerted neuroprotective effects in experimental intracerebral hemorrhage. 20 In addition, similar results were found in ischemic stroke using siRNA knockdown of NLRC4. 14 In the current study, serum NLRC4 levels were independently correlated with serum C-reactive protein levels.…”
Section: Discussionsupporting
confidence: 67%
“…NLRC4 is a very important component of inflammasome. 19 NLRC4 was highly expressed in brain tissues of mice after intracerebral hemorrhage in a time-dependent manner, with peaking at post-hemorrhage 24 h. 20 In addition, the highest expression of rat NLRC4 in ischemia area was revealed at 4h of transient cerebral ischemia/reperfusion. 21 Moreover, NLRC4 was dominantly located in neurons after animal cerebral ischemia 22 and in glial cells under lysophosphatidylcholine, a molecule associated with neurodegeneration and demyelination.…”
Section: Discussionmentioning
confidence: 96%
“…NLRC4 is a member of them and is responsible to process prointerleukin-1beta and pro-interleukin-18 into a maturation state to promote inflammation (19). A previous experimental study showed that NLRC4 expressions were enhanced in a timedependent manner following ICH, and peaked at 24 h following ICH (20). Another animal study demonstrated that there was a substantial upregulation of NLRC4 expressions after cerebral ischemia and NLRC4 was mainly localized in neurons (21).…”
Section: Discussionmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH), defined as a brain injury caused by acute bleeding into the brain parenchyma from a ruptured cerebral blood vessel [1], is arguably the most lethal form of acute stroke [2]. The early-term mortality of ICH is around 40%, with no significant improvement over the past three decades [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nlrc4 could be upregulated after arterial blood was drawn from rats and injected into the basal ganglia (to simulate the ICH model), and the elimination of Nlrc4 was demonstrated to attenuate neuronal death, cerebral swelling and neurological deficits following ICH [8]. Additionally, the inhibition of Nlrc4-dependent pyroptosis was proved to be beneficial for neurological function [2]. However, the mechanism of Nlrc4-dependent neuronal pyroptosis in ICH remains unclear and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%